The effect of ethanol wet bonding technique on postoperative hypersensitivity of Class II composite restorations: A randomized trial - Alireza Boruziniat; Sanaz Alizadeh; Mahshid Gifani; Zafer C Cehreli; Yeganeh Khazaei (Wolters Kluwer Medknow Publications, 2021)
Background: To evaluate the effect of Ethanol Wet Bonding Technique (EWBT) on postoperative hypersensitivity (POH) of composite restorations in premolar teeth. Materials and Methods: In this randomized trial, 24 patients with at least three proximal carious lesions with similar axial depth and position of gingival floor in their premolars were enrolled. Following cavity preparation, the teeth were randomly assigned to one of three groups: (1) Class II resin-based composite (RBC) restoration using an etch-and-rinse adhesive + wet bonding technique (Control); (2) RBC restoration using EWBT + hydrophobic adhesive; and (3) RBC restoration using EWBT + hydrophilic adhesive. Tooth hypersensitivity was evaluated before and 1, 3, 7, 14 and 30 days after treatment according to the Visual Analog Scale. Data were analyzed statistically with Kruskal-Wallis and Friedman tests (P = 0.05). Results: All teeth showed similar levels of hypersensitivity after treatment (both P > 0.05). Furthermore, there was no difference between POH levels of the test and control groups at any control period (P < 0.05). Friedman test indicated that the POH significantly reduced within time in all groups (P < 0.05). Conclusion: Application of ethanol-wet bonding technique, either with hydrophobic or hydrophilic adhesives did not affect the POH of Class II composite restorations in premolars.